Pengaruh Strategi Pembelajaran Koperatif Tipe Investigasi Kelompok Terhadap Hasil Belajar Pkn Siswa Kelas VI SD - Mandriani, Ni Nyoman (Jurnal Ilmiah Sekolah Dasar, 2018)
This study aims to determine the differences in learning outcomes between students who take the Civics with cooperative learning strategies and investigations group of students who take lessons with conventional teaching model in class VI students of SD Negeri 2 Datah, Abang, Karangasem academic year 2016/2017.This research is a quasi experimental study . The study populationwas all students of class XI of  SD Negeri 2 Datah Karangasem academic year 2016/2017 , amounting to 115 people . The study sample is a class VI student of  SD N 2 Datah which were 25 students of class VI. Data on students' learning outcomes Civics obtained through a written test conducted at the end of the lesson . The data obtained were then collected and analyzed using descriptive statistical analysis and inferential statistics (test ).Based on the analysis of data , obtained thit = 13.20 and ttab ( at significance level of 5 % ) = 2.00. Obtained average (x) count , the experimental group was 26.9 and the control group was 16.73 . This means that the experimental > control , so it can be concluded that the model of learning group investigastion  affect learning outcomes Civics class VI students of  SD N 2 Datah regency of Karangasem